PERHITUNGAN BEBAN PENDINGIN PADA COLD STORAGE UNTUK PENYIMPANAN IKAN TUNA PADA PT.X - Siagian, Saut (Bina Teknika, 2017)
One application is the refrigeration system to cool freshness of the fish so that the fish can survive longer. An engine coolant is used to store and cool fish called cold storage. While the special machine used to freeze fish quickly (1-2 hours) is called Air Blast Freezer (ABF). The purpose of freezing the fish in the ABF is to inhibit the growth of microorganisms that exist in fish that could not breed, then the fish is stored and further chill in cold storage. Cold storage and ABF is in Cirebon spend huge electricity costs when the number of fish average - average stored in cold storage is less than 1 ton per day. To that through this thesis the author seeks to examine and find solutions to these problems.How that is done to be able to analyze the problems of the first was to measure and quantify the performance of the existing cooling system. Then compare it with the cooling load conditions as a result of the heat is transmitted to the evaporator. Because if the load is too large cooling will also result in a heavy compressor work and result in large power consumption as well.